Maternal exposure to NO2 enhances airway sensitivity to allergens in BALB/c mice through the JAK-STAT6 pathway. (June 2018) - Yue, Huifeng; Yan, Wei; Ji, Xiaotong; Zhang, Yingying; Li, Guangke; Sang, Nan
Abstract: Previous studies have indicated that nitrogen dioxide (NO2 ) exposure could increase airway sensitivity to allergens for children. Recently, fetal stress was proposed as a crucial factor for allergic airway response occurring in offspring. Considering that there is inadequate evidence linking maternal NO2 exposure to offspring airway sensitivity to allergens, pregnant Balb/c mice were exposed daily to 2.5 ppm NO2 throughout the gestation period; then, the offspring were challenged to an allergen (ovalbumin, OVA) to evaluate airway sensitivity. For air + saline group and air + OVA group, offspring mice were maternally exposed to clean air followed by treatment with saline and OVA, respectively, in adulthood. For NO2 + saline group and NO2 + OVA group, offspring mice were maternally exposed to NO2 followed by treatment with saline and OVA, respectively, in adulthood. The results showed that maternal NO2 exposure increased the level of OVA-immunoglobulin (Ig) E in serum and caused airway hyper-responsiveness and pathological changes in offspring. Furthermore, maternal NO2 exposure altered the expression of pro-inflammatory factors and impaired the T helper (Th) 1/Th2 balance. In addition, janus kinase)-signal transducer and activator of transcription 6 pathway participated in OVA-induced airway sensitivity of offspring. Our study showed that the potential risk of airway sensitivity to allergens in offspring is enhanced by maternal NO2 exposure and proposed a possible mechanism for preventing, alleviating, and evaluating the outcomes in polluted environments. Highlights: Maternal NO2 exposure enhances OVA-IgE and AHR in offspring to allergens. Maternal NO2 exposure disrupts the balance of Th1/Th2 in offspring to allergens. Maternal NO2 exposure activates the JAK-STAT6 pathway in offspring to allergens.